Fibrinolytic Activity of Recombinant Mutant Streptokinase - Mobarrez, Mahboobeh; Bandehpour, Mojgan; Salehmoghadam, Massoud; Kazemi, Bahram (Novelty in Biomedicine, 2015)
Background: Streptokinase is a bacterial protein produced by different beta hemolytic streptococci and widely used in thrombolytic treatment. The main disadvantage of using streptokinase is antibody formation which causes allergic reaction to neutralize effects of streptokinase therapy. Aim of this study was investigate of recombinant mutant streptokinase fibrinolytic activity. Materials and Methods: In this study recombinant mutant streptokinase without 42 amino acids from the C terminal region was purified by affinity S-Tag column chromatography and its fibrinolytic activity was studied. Results: The concentration of expressed and purified protein was 10 mg/ml. Its enzyme activity was assayed using zymography, radial caseinolytic activity and fibrin plate test methods and estimated quantitatively by casein digestion method compared to a commercial form. Conclusion: It was found that this product had the more volume and more enzymatic activity.